Erosive wear behaviour of HVOF-sprayed Ni-20Cr2O3 coating on pipeline materials. (November 2020) - Bansal, Anuj; Goyal, Deepak Kumar; Singh, Prabhjot; Singla, Anil Kumar; Gupta, Munish Kumar; Bala, Niraj; Kolte, Jayant; Setia, Gautam
Abstract: The present work describes the application of High-Velocity oxy-fuel spray process with Ni-20Cr2 O3 powder deposition on the various pipeline steels namely SS 202, SS 304, and mild steel. The slurry erosion wear tests were performed on coated and uncoated steels by considering slurry concentration, impact velocity, and erosion time as input parameters. It was concluded that for all materials, rpm (impact velocity of erodent's) influences on erosion wear the most. It was also noticed that the erosion resistance has been improved with SS 202 steel followed by to SS 304 and mild steel. Further, Ni-20Cr2 O3 coatings showed maximum enhancement in slurry wear resistance of mild steel, followed by SS 304 steel and SS 202 steel. Highlights: Application of High-Velocity oxy-fuel spray process with Ni-20Cr2 O3 powder deposition was investigated. Slurry erosion wear tests were performed on different pipeline steels such as SS 202, SS 304, and Mild steel. Influence of three parameters namely slurry concentration, impact velocity, and erosion time was investigated. Ni-20Cr2 O3 coatings showed maximum enhancement in slurry wear resistance of Mild steel.